2009 Physics Education Research Conference : Ann Arbor, MI, 29-30 July 2009 - Physics Education Research Conference (2009 Ann Arbor, Mich.); Sabella, Mel; Henderson, Charles; Singh, Chandralekha; American Institute of Physics (Melville, NY : American Institute of Physics, 2009)
Includes bibliographical references and index